2018
DOI: 10.14419/ijet.v7i3.14326
|View full text |Cite
|
Sign up to set email alerts
|

Map of Jordan governorates wind distribution and mean power density

Abstract: The Renewable energy potential in Jordan is enormous as it lies within the top of the world countries renewable resources. Electricity demand in Jordan plays a major role in the high amount of energy requring to cover the needs of heating, cooling, lighting, etc. For that, the availability of the wind distribution information becomes essential to help in the design and building of the wind energy application. In this study, a wind distribution map is provided of all Jordan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…But Jordan is blessed with an abundance of solar energy which is evident from the annual daily average solar irradiance (average insolation intensity on a horizontal surface) ranges between 4-8 kWh/m², which is one of the highest in the world. This corresponds to a total annual of 1400-2300kWh/m²; with the average sunshine duration is more than 300 days per year [1][2][3][4][5][6][7]. Nowadays, renewable energy systems are being utilized extensively to generate electricity due to its positive features [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…But Jordan is blessed with an abundance of solar energy which is evident from the annual daily average solar irradiance (average insolation intensity on a horizontal surface) ranges between 4-8 kWh/m², which is one of the highest in the world. This corresponds to a total annual of 1400-2300kWh/m²; with the average sunshine duration is more than 300 days per year [1][2][3][4][5][6][7]. Nowadays, renewable energy systems are being utilized extensively to generate electricity due to its positive features [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The greatest values of k and c parameters may be found at Aqaba Airport. Alrwashdeh [22] employed mathematics and a world wind atlas to produce a wind distribution map of all Jordan provinces and the most suitable sites for wind farms. It was observed that when the hub's elevation is increased from 50 to 200 meters, the mean power density increases.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to Jordan, we find that it has been blessed with a huge amount of solar energy sufficient to meet the needs of energy because Jordan receives more than 300 sunny days throughout the year with a very bright solar radiation rate compared to neighboring countries and countries of the world [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In this context, there is an urgent need to support investment in the renewable energy sector in various countries of the world and in Jordan in particular because investment in this sector is still very low and there is a lacks in the supporting from different sectors inside the Jordan [4,12,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The availability of alternative energy sources is not enough to take the advantage of achieving the goal of disposal of traditional energy sources, but it is desirable that technology is available to assist in the optimization of renewable energy sources. Renewable energy is a promising candidate to replace the traditional energy for that we should be mentioned that there are many ways to exploit the solar energy which is the direct way through photovoltaic cells, which convert solar energy through radiation Pick-up on photovoltaic cells into electrical energy, as well as indirect method available is to convert solar energy by get the benefit through using the usual falling of the solar radiation and convert it to heating the water to produce steam and makes it triggers various turbines to generate electricity as a by-final of this process [5][6][7][8][9][10][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%